16 Ounces, I hope this helps, Mark me brainliest
<span>9a + -3(2a + -4) = 15
Reorder the terms:
9a + -3(-4 + 2a) = 15
9a + (-4 * -3 + 2a * -3) = 15
9a + (12 + -6a) = 15
Reorder the terms:
12 + 9a + -6a = 15
Combine like terms: 9a + -6a = 3a
12 + 3a = 15
Solving
12 + 3a = 15
Solving for variable 'a'.
Move all terms containing a to the left, all other terms to the right.
Add '-12' to each side of the equation.
12 + -12 + 3a = 15 + -12
Combine like terms: 12 + -12 = 0
0 + 3a = 15 + -12
3a = 15 + -12
Combine like terms: 15 + -12 = 3
3a = 3
Divide each side by '3'.
a = 1
Simplifying
a = 1</span>
Step-by-step explanation:
as the other guy say it a for real